Evaluasi Pembelajaran Fisika Dasar Menggunakan Model Provus di Universitas - Cindy Regina Liputo; Masri Kudrat Umar; Dewi Diana Paramata (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
There are various issues faced by college students while learning in college, which is why it is important to conduct evaluations to measure the success rate of the learning system. This research purposes to intended to analyze the problems encountered in learning so that solutions can be found, moreover the evaluation aims to assess the success of leraning that has been implemented. This research uses a qualitative and evaluative method of approach (discrepancy model's) with 4 evaluation dimensions (design, installation, process, and product). The result shows that overall, that design evaluation and installation evaluation are in the good category, process evaluation needs to be improved due to decreased attendance in the learning process, and product evaluation is considered good.